2017
DOI: 10.1007/s10488-017-0795-0
|View full text |Cite
|
Sign up to set email alerts
|

How Intervention and Implementation Characteristics Relate to Community Therapists’ Attitudes Toward Evidence-Based Practices: A Mixed Methods Study

Abstract: Therapists’ perceptions toward evidence-based practices (EBPs) are important in implementation efforts, however little is known about characteristics of EBPs associated with more positive attitudes. This mixed-methods study examined how intervention and implementation characteristics of six EBPs related to therapist attitudes. Quantitative analysis of 793 cross-sectional surveys revealed that therapists endorsed more positive attitudes toward EBPs with 1) prescribed session content and order and 2) required co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
56
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 52 publications
4
56
0
Order By: Relevance
“…Indeed, studies have found program leaders to have positive perceptions of MAP due to the wide range of cases or clients that MAP can be used with ( 39 , 43 ). In addition, MAP, TF-CBT, and CPP require ongoing consultation, which may have implications for their sustained delivery ( 44 ). By contrast, SS and TP do not require ongoing consultation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies have found program leaders to have positive perceptions of MAP due to the wide range of cases or clients that MAP can be used with ( 39 , 43 ). In addition, MAP, TF-CBT, and CPP require ongoing consultation, which may have implications for their sustained delivery ( 44 ). By contrast, SS and TP do not require ongoing consultation.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also apparent that therapists have distinctive perceptions of different EBPs. In contexts where therapists are trained in multiple EBPs, therapist opinions concerning the appeal, utility and limitations of specific interventions vary (Barnett et al, in press; Reding et al, 2014). Therefore, it is plausible that the likelihood that a therapist makes a modification to an EBP that augments or reduces or reorders the content is determined by their perceptions toward that specific practice, rather than their attitudes toward EBPs in general.…”
mentioning
confidence: 99%
“…There are some attitudes, related to the practice and teaching of clinical psychology, that explain why some professionals prefer CAP instead of EBP (Gallo & Barlow, 2012;Stewart, Chambless, & Baron, 2012). For example, many clinicians are emotionally exhausted by high workloads and do not have the time to search for evidence-based interventions (Gallo & Barlow, 2012;Barnett, Brookman-Frazee, Regan, Saifan, Stadnick, & Lau, 2017). Some of them feel overwhelmed by the massive amount of existing information about EBP and see the search for relevant research outcomes as an endless endeavour (Gallo & Barlow, 2012), while many find the technical language used as greatly problematic -especially the statistical jargon of academic articles (Backer, 2000).…”
Section: Pragmatic Limitationsmentioning
confidence: 99%